Mosque management at Mara University of Technology Kota Kinabalu Campus Sabah ( Pusat Islam Wahdatul Ummah ) / Sudirman Sabdan... [et al.] - Sabdan, Sudirman; Hj Shariful, Syed Dahlan (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2001)
We used a few methods to collect the information about the Mosque Management -in UiTM Kota Kinabalu Campus. Basically, we were using the questionnaire and interview method. The main objective of research is to identify the Mosque Management in UiTM in a ce1tain aspect. Through these researches, we should know, how the management plays their role as we11 as the committee performing in their work regards to job description within organization of Mosque Management. Here, we make an interview and questionnaires in process of collecting data among people such as members of Mosque Management, staffs and UiTM Administrative Body, which in our opinion should assist some correct information. The important thing is that, we will acknowledge about the inter-related among the Mosque Management and members together plays the role to achieve objectives. Furthermore, to measured how effective and efficient it is in managed activities in order to fulfill the people needs such as students and little information about organization of Mosque Management of establishment.